The effects of virtual reality on stroke rehabilitation: A systematic review - José Eduardo Pompeu; Thais Helena Alonso; Igor Bordello Masson; Sandra Maria Alvarenga Anti Pompeu; Camila Torriani-Pasin (Desafio Singular, 2014)
This study aimed to perform a systematic review to verify the effects of virtual reality (VR) on the rehabilitation of stroke patients. The search was conducted in the electronic databases Medline, Lilacs, Scielo and PubMed, from 2004 to 2012. The keywords selected for the search were: virtual reality, video game, stroke, physiotherapy, rehabilitation. It was found 893 articles, and at the end of selection, nine studies were included. The results showed that training with VR may contribute to the rehabilitation of stroke patients. The selected studies involved the use of seven different VR systems for training of functions: gait, balance, upper limb function, cognition and perception. Furthermore, depending on the function trained, the authors selected different assessment methods. However, even in the studies with similar functions assessed it was found different measurement techniques. The conclusion was that VR can promote positive effects on rehabilitation of post stroke patients. Despite promising results, further studies are needed with larger numbers of subjects and better methodological quality.